Proceedings of the International Conference on Tourism, Gastronomy, and Tourist Destination (ICTGTD 2016) 2017
DOI: 10.2991/ictgtd-16.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Food Blogger to the Intention of Consuming Healthy Food

Abstract: Abstract-The purpose of this study is to examine consumer behavior towards review and recommendation of food blogger regarding healthy eating lifestyle and to know whether there is a relation between food bloggers review and recommendation to healthy eating and consumer behavioral intention. The unit analysis in this research is people who know and read about food blog, with 192 valid questionnaires from respondents that reside in Jakarta, Bandung and Bogor. Data were analyzed using SPSS software.The result sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Consequently, companies start using this tool to make consumers more engaged with the brand and increase their purchase intention (Fuchs, 2021). According to Nathalia et al (2017), the interaction between influencers and followers/customers positively affects the attitudes towards organic products. Moreover, effective interaction between influencers and followers results in a positive attitude towards influencers (Yuan and Lou, 2020) and a higher purchase intention (Sokolova and Kefi, 2019).…”
Section: Hypothesesmentioning
confidence: 99%
“…Consequently, companies start using this tool to make consumers more engaged with the brand and increase their purchase intention (Fuchs, 2021). According to Nathalia et al (2017), the interaction between influencers and followers/customers positively affects the attitudes towards organic products. Moreover, effective interaction between influencers and followers results in a positive attitude towards influencers (Yuan and Lou, 2020) and a higher purchase intention (Sokolova and Kefi, 2019).…”
Section: Hypothesesmentioning
confidence: 99%
“…In this study, based on the study of Wang (2011), the variables of encouraging tasting behavior (providing experience and creating empathy), creating taste awareness (providing images, providing information and guidance) and facilitating interpersonal interaction (social impact and cyber community effect), The main reasons for the YouTube food channel to affect the tasting behavioral intentions of the followers were determined and 3 of the 7 hypotheses formed in this context were accepted. It has been taken into consideration in previous studies, that the effect of both dimensions of the stimulating taste behavior variable (providing experience and creating empathy) on the behavioral intention to taste has been demonstrated by previous studies (Kim et al, 2009;Lim et al, 2019;Lin & Huang, 2006;Nathalia et al, 2016;Wang, 2011) reveal a parallelism. It has been determined that the effect of the dimensions of creating a taste awareness variable on the taste and the behavioral intention of providing a guide differ from previous studies (Cankül & Ar, 2018;Wang, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…14, 17 Food shows delivered by food vloggers on YouTube attract teenagers' attention and it is evident that teens tend to choose the food vlogger channel to be a source of information and advice. 13, 18 The results showed that teenagers were more receptive to influencers on YouTube compared to celebrities on television. 19 Food content videos that air on YouTube can affect the desire of teenagers to try food served by food vloggers.…”
Section: Sub-themementioning
confidence: 98%